Examining political risk in service offshoring strategies - Hansen, Carsten (Cranfield University, 2015)
This research investigates political risk in the context of service offshoring and the corresponding impact on risk management decisions. The first stage of the study uses the Repertory Grid Technique (RGT), to explore key post-contract political risks experiences within offshore outsourcing activities. Twelve key political risks affecting offshore outsourcing decisions are identified, and the moderating effect of offshoring activity types (BPO, ITO or KPO) on political risk exposure and impact perceptions is highlighted. The research also explores the conditioning effect of industry specific exposure to political risk and enhances the explanatory ability of the Transaction Cost Economics (TCE) constructs, offering a re-operationalization of the political risk component of external uncertainty. The second stage of the research introduces a series of hypotheses between offshoring flows and political risk profiles, and applies multiple regression to analyse political risk affecting offshore activities in low cost countries across contract-based offshoring engagements and FDI. The findings highlight that political risk is a genuine business concern for offshore contract-based outsourcing modalities, and identify concerns with Intellectual Property protection, Quality of Bureaucracy and Corruption as key considerations affecting location decisions in low-cost countries. The research further suggests a positive relationship between strong country level institutional and regulatory systems and high knowledge content in offshoring engagements. From a practical perspective, the research highlights the need for managerial tools to determine diversified firm and industry specific political risk impact on global service outsourcing engagements. The key practical contribution is the development of differentiated political risk typologies that can capture the nuances of external risks in offshoring, allowing for more accurate risk assessment of offshoring decisions.
Keywords: Political Risk; Offshore Outsourcing; Low-cost country sourcing; Service Offshoring; Foreign Direct Investment (FDI); Transaction Cost Theory; Repertory Grid Analysis; Multiple Regression Analysis